Sociolinguistic Features of Facebook Shares of College Students - Separa, Lenis Aislinn C.; Fontillasc, Lemuel R. (International Journal of Psychosocial Rehabilitation, 2020)
Since it is a known fact that the young generation is hooked to a variety of gadgets together with internet connectivity, social media has been an everyday part of their lives. Updating of statuses in their own profile pages becomes now an integral means of self-expression in the cyber community worldwide. This study aims to investigate the trends and patterns in their online communication messages. With an informed consent of the college students who were selected through purposive sampling, content analysis of 83 submitted corpus of their Facebook posts was done. Results reveal that Facebook users have a variety of intentions when sharing updates in their status posts which suggests both positive and negative intentions. Facebook users update their walls with message contents that are addressed to oneself, other people, and even to non-human target receivers. The openness of thoughts and directness of speech in the messages suggests the comfort and security students feel when sharing in Facebook. As the tendencies in online messaging were presented, it is recommended that media literacy be integrated in the curriculum across different programs.